Delayed Orbital Apex Syndrome in the Post-Reconstructed Orbit. Issue 5 (July 2020) - Zhao, Yiping; Li, Zhengkang; Deng, Yuan
Abstract : Abstract: Delayed orbital apex syndrome (OAS) is rare during orbital blowout fracture reconstruction. A 30-year-old woman fractured the right orbital floor in a fall and undergone repairing operation 2 weeks later. After severe sneezing on postoperative day 10, she gradually arose vision loss, ophthalmoplegia, ptosis with a dilated and fixed pupil within few hours, then consulted our department and was diagnosed as OAS. Computed tomography scan showed displaced implant and retrobulbar emphysema resulting in a constellation of compression to orbital apex. Therefore, an exploratory operation was engaged to reposition the implant and reduce the emphysema concurrent with mega-dose steroids. The patient regained vision immediately and resolved all symptoms at the 6 months follow-up.